PENINGKATAN HASIL BELAJAR MODEL DISCOVERY LEARNING BERBANTUAN MEDIA KARTU KUARTET DI SEKOLAH DASAR - Moh Jauharul Fanani; Much Arsyad Fardani; Sudjadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve learning outcomes in the subject of Natural and Social Sciences (IPAS) through the implementation of the Discovery Learning model assisted by cultural quartet card media. The research subjects were 16 fourth-grade students at SD Negeri 1 Kalirejo. This research was a Classroom Action Research (CAR) conducted in two cycles, each consisting of the stages of planning, action, observation, and reflection. In the pre-cycle stage, learning was still teacher-centered and showed low student achievement, with only 25% of students reaching the minimum mastery criteria. After implementing the Discovery Learning model combined with the cultural quartet card media, students' active involvement in the learning process increased. The results showed a significant improvement: classical learning mastery rose from 68.75% in cycle I to 81.25% in cycle II. The average student score also increased from 75.37 to 81.57. It can be concluded that the use of the Discovery Learning model assisted by cultural quartet card media is effective in improving IPAS learning outcomes and supports active and meaningful learning in accordance with the Merdeka Curriculum principles